2012
DOI: 10.1155/2012/575387
|View full text |Cite
|
Sign up to set email alerts
|

New Traveling Wave Solutions of the Higher Dimensional Nonlinear Partial Differential Equation by the Exp‐Function Method

Abstract: We construct new analytical solutions of the (3+1)-dimensional modified KdV-Zakharov-Kuznetsev equation by the Exp-function method. Plentiful exact traveling wave solutions with arbitrary parameters are effectively obtained by the method. The obtained results show that the Exp-function method is effective and straightforward mathematical tool for searching analytical solutions with arbitrary parameters of higher-dimensional nonlinear partial differential equation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
51
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(51 citation statements)
references
References 33 publications
0
51
0
Order By: Relevance
“…With the development of symbolic computation software, likeMaple, many numerical and analytical methods to search for exact solutions of NLEEs have attracted more attention. As a result, the researchers developed and established many methods, for example, Cole-Hopf transformation [8], Tanh-function method [9][10][11][12][13], Inverse scattering transform method [14], Hirota method [15], Backlund transform method [16], Variational iteration method [17,18], Exp-function method [19][20][21][22][23], Extended tanh-method [24][25][26], Homogeneous balance method [27,28] and F-expansion method [29,30] are used for searching the exact solutions. Lately, Wang et al [31] introduced a direct and concise method, called (G'/G)-expansion method and demonstrated that it is a powerful method for seeking analytic solutions of NLEEs.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of symbolic computation software, likeMaple, many numerical and analytical methods to search for exact solutions of NLEEs have attracted more attention. As a result, the researchers developed and established many methods, for example, Cole-Hopf transformation [8], Tanh-function method [9][10][11][12][13], Inverse scattering transform method [14], Hirota method [15], Backlund transform method [16], Variational iteration method [17,18], Exp-function method [19][20][21][22][23], Extended tanh-method [24][25][26], Homogeneous balance method [27,28] and F-expansion method [29,30] are used for searching the exact solutions. Lately, Wang et al [31] introduced a direct and concise method, called (G'/G)-expansion method and demonstrated that it is a powerful method for seeking analytic solutions of NLEEs.…”
Section: Introductionmentioning
confidence: 99%
“…Many powerful method have been obtainable for instance the exp(-Φ(ξ))-expansion method (Khan et al, 2013a;Islam et al, 2014); the jacobi elliptic function method (Ali, 2011); the homogeneous balance method (Wang, 1995;Zayed et al, 2004); the modified simple equation method (Jawad et al, 2010;Khan and Akbar, 2013b;Zayed and Ibrahim, 2012;Akter and Akbar, 2015); the (G′/G)-expansion method (Wang et al, 2008;Zayed, 2010;Akbar et al, 2012b;Zayed and Gepreel, 2009;Akbar and Ali, 2011;Shehata, 2010;Akbar et al, 2012a;Mirzazadeh et al, 2014;; the improve (G′/G)-expansion method (Zhang et al, 2010); the extended(G′/G)-expansion method (Roshid et al, 2014a;; the generalized (G′/G)-expansion method 2014c); the novel (G′/G)-expansion method (Hafez et al, 2014); the homotopy perturbation method (Mohyud-Din et al, 2011a;2011b;2011c); the variational method (He, 1997;Abbasbandy, 2007;Arife and Yildirim, 2011;Abdou and Soliman, 2005); the exp-function method (Akbar and Ali, 2012;He and Wu, 2006;Naher et al, 2012); the truncated painleve expansion method (Weiss et al, 1983); the asymptotic method (He, 2008); the Hirota's bilinear transformation method (Hirota, 1973;Hirota and Satsuma, 1981); the tanhfunction method (Abdou, 2007;…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several methods have been established for investigating nonlinear PDEs to obtain exact solutions. For example, the Hirota's bilinear transformation method [1], the B cklund transformation method [2], the Jacobi elliptic function expansion method [3], the generalized Riccati equation method [4,5], the homogeneous balance method [6], the F-expansion method [7], the Exp-function method [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%